Ancient genomes in South Patagonia reveal population movements associated with technological shifts and geography - Nakatsuka, Nathan; Luisi, Pierre; Motti, Josefina M. B.; Salemme, Monica; Santiago, Fernando; D'Angelo del Campo, Manuel D.; Vecchi, Rodrigo J.; Espinosa Parrilla, Maria Yolanda; Prieto, Alfredo; Adamski, Nicole; Lawson, Ann Marie; Harper, Thomas K.; et al. (My University, 2020)
Archaeological research documents major technological shifts among people who have lived in the southern tip of South America (South Patagonia) during the last thirteen millennia, including the development of marine-based economies and changes in tools and raw materials. It has been proposed that movements of people spreading culture and technology propelled some of these shifts, but these hypotheses have not been tested with ancient DNA. Here we report genome-wide data from 20 ancient individuals, and co-analyze it with previously reported data. We reveal that immigration does not explain the appearance of marine adaptations in South Patagonia. We describe partial genetic continuity since similar to 6600 BP and two later gene flows correlated with technological changes: one between 4700-2000 BP that affected primarily marine-based groups, and a later one impacting all <2000 BP groups. From similar to 2200-1200 BP, mixture among neighbors resulted in a cline correlated to geographic ordering along the coast.
Keywords: Cline (biology)